Yttrium-based protective film, method for producing same, and member
By controlling the porosity and Vickers hardness in the yttrium protective film and using ion-assisted evaporation method, the existing yttrium protective film has been solved inadequate plasma resistance and appearance problems, and the corrosion resistance and appearance are achieved.
Patent Information
- Application Number
- CN202380060506.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-01
- Filing Date
- 2023-06-21
- Publication Date
- 2025-03-28
AI Technical Summary
The existing yttrium protective film is insufficiently corrosion-resistant when facing plasma, and is prone to appearance problems such as cracks and wrinkles, which makes it unsuitable for direct use.
By controlling the porosity of less than 0.5 volume %, the Vickers hardness is 800 HV or more in the yttrium protective film, and ion-assisted evaporation method is used during the manufacturing process, ions are irradiated in vacuum and the Y2O3 evaporation source is adhered to the substrate, thereby forming a dense and hard yttrium protective film.
It realizes the plasma resistance and appearance of the yttrium protective film, avoids corrosion and crack problems, and is suitable for use in semiconductor equipment manufacturing and other fields.
Smart Images

Figure CN119731366A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a yttrium protective film and a method for manufacturing the same and a component thereof. Background Art
[0002] When manufacturing semiconductor devices, for example, the surface of a semiconductor substrate (silicon wafer) is micro-processed in a chamber by dry etching using plasma of a halogen gas, or the chamber after the semiconductor substrate is removed is cleaned using oxygen plasma after dry etching.
[0003] At this time, the parts exposed to the plasma in the chamber may be corroded, and the corroded parts may fall off from the corroded parts in the form of particles. The fallen particles (grains) may adhere to the semiconductor substrate and become foreign matter that causes defects in the circuit.
[0004] Therefore, conventionally, a protective film containing yttrium oxide (Y 2 O 3 ) (yttrium protective film) has been known as a protective film for protecting components exposed to plasma.
[0005] Patent Document 1 discloses a thermally sprayed film containing yttrium oxide formed by thermal spraying.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2018-76546 Summary of the invention
[0009] The present inventors have conducted studies and found that conventional yttrium protective films have insufficient plasma resistance (corrosion resistance to plasma).
[0010] In addition, the appearance of the yttrium protective film may be poor (for example, cracks or wrinkles may occur in the yttrium protective film). In this case, it is not suitable to use the yttrium protective film as it is, depending on the application.
[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an yttrium protective film having excellent plasma resistance and appearance.
[0012] The present inventors have conducted intensive studies and have found that the above-mentioned object can be achieved by adopting the following configuration, thereby completing the present invention.
[0013] That is, the present invention provides the following [1] to
[22] .
[0014] [1] An yttrium protective film comprising yttrium oxide, having a porosity of less than 0.5% by volume and a Vickers hardness of 800 HV or more.
[0015] [2] The yttrium protective film according to [1] above, wherein the thickness is 0.3 μm or more.
[0016] [3] The yttrium protective film according to [1] or [2] above, wherein the thickness is 15 μm or less.
[0017] [4] The yttrium protective film according to any one of [1] to [3] above, wherein the crystallite size is 40 nm or less.
[0018] [5] The yttrium protective film according to any one of [1] to [4] above, wherein the crystallite size is 6 nm or more.
[0019] [6] The yttrium protective film according to any one of [1] to [5] above, wherein the orientation degree of the (222) crystal plane of Y2O3 is 50% or more.
[0020] [7] The yttrium protective film according to any one of [1] to [6], wherein the number of hydrogen atoms is 5.0×10 21 Pieces / cm 3 the following.
[0021] [8] The yttrium protective film according to any one of [1] to [7] above, wherein the compressive stress is 100 to 1700 MPa.
[0022] [9] A component comprising: a substrate; and the yttrium protective film according to any one of [1] to [8] above, which is disposed on a surface of the substrate, namely, a film-forming surface.
[0023]
[10] A component according to [9] above, wherein the substrate is composed of at least one selected from carbon, ceramics and metals, the ceramic is at least one selected from glass, quartz, alumina, aluminum nitride, cordierite, yttrium oxide, silicon carbide, Si-impregnated silicon carbide, silicon nitride, sialon and aluminum oxynitride, and the metal is at least one selected from aluminum and aluminum-containing alloys.
[0024]
[11] The component according to [9] above, wherein the substrate is made of aluminum oxide.
[0025]
[12] The component according to [9] above, wherein the substrate is made of quartz.
[0026]
[13] The component according to any one of [9] to
[12] above, wherein the surface roughness of the film-forming surface is less than 1.0 μm in terms of arithmetic mean roughness Ra.
[0027]
[14] The component according to any one of [9] to
[13] above, wherein the surface roughness of the film-forming surface is 0.01 μm or more in terms of arithmetic mean roughness Ra.
[0028]
[15] The component according to any one of [9] to
[14] above, wherein the maximum length of the film-forming surface is 30 mm or more.
[0029]
[16] A component according to any one of [9] to
[15] above, wherein there is one or more base layers between the substrate and the yttrium protective film, and the base layer contains at least one oxide selected from Al2O3, SiO2, Y2O3, MgO, ZrO2, La2O3, Nd2O3, Yb2O3, Eu2O3 and Gd2O3.
[0030]
[17] The component according to
[16] above, wherein there are two or more base layers between the substrate and the yttrium protective film, and the oxides in adjacent base layers are different from each other.
[0031]
[18] A component according to any one of [9] to
[17] above, wherein the substrate has a first film-forming surface with a specified maximum length and a second film-forming surface different from the first film-forming surface as the film-forming surface, the angle between the first film-forming surface and the second film-forming surface is 20° to 120°, and the area of the second film-forming surface is less than 60% of the total area of the film-forming surface.
[0032]
[19] The component according to any one of [9] to
[18] above, which is used inside a plasma etching device or a plasma CVD device.
[0033]
[20] A method for manufacturing a yttrium protective film, which is a method for manufacturing a yttrium protective film as described in any one of [1] to [8] above, wherein an evaporation source is evaporated and attached to a substrate in a vacuum while irradiating the substrate with ions of at least one element selected from oxygen, argon, neon, krypton and xenon, wherein Y2O3 is used as the evaporation source.
[0034]
[21] The method for producing a yttrium protective film according to
[20] above, wherein the substrate is heated at 300° C. or higher before the evaporation source is attached to the substrate.
[0035]
[22] A method for manufacturing an yttrium protective film according to
[20] or
[21] above, wherein before the evaporation source is attached to the substrate, one or more base layers are formed on the surface of the substrate, and the base layer contains at least one oxide selected from Al2O3, SiO2, Y2O3, MgO, ZrO2, La2O3, Nd2O3, Yb2O3, Eu2O3 and Gd2O3.
[0036] According to the present invention, it is possible to provide an yttrium protective film having excellent plasma resistance and appearance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic diagram showing an example of components.
[0038] Figure 2 This is a schematic diagram showing a ring-shaped substrate with half of it cut away.
[0039] Figure 3 1 is a schematic diagram showing a part of the cross section of another annular base material.
[0040] Figure 4 1 is a schematic diagram showing a part of the cross section of still another annular base material.
[0041] Figure 5 This is a schematic diagram showing an apparatus used for producing the yttrium protective film.
[0042] Figure 6 This is the XRD pattern of the yttrium protective film of Example 1.
[0043] Figure 7 This is a surface SEM photograph of the yttrium protective film of Example 1.
[0044] Figure 8 This is a cross-sectional SEM photograph of the yttrium protective film of Example 1. DETAILED DESCRIPTION
[0045] The meanings of the terms in the present invention are as follows.
[0046] The numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0047] [Yttrium protective film]
[0048] The yttrium protective film of the present embodiment contains yttrium oxide, has a porosity of less than 0.5% by volume, and has a Vickers hardness of 800 HV or more.
[0049] Hereinafter, the yttrium protective film is also simply referred to as a "protective film", and the yttrium protective film (protective film) of the present embodiment is also referred to as a "present protective film".
[0050] The protective film is excellent in plasma resistance and appearance.
[0051] Hereinafter, the present protective film will be described in more detail.
[0052] 〈Vickers Hardness〉
[0053] Because the present protective film has excellent plasma resistance, the Vickers hardness of the present protective film is 800 HV or more, preferably 1000 HV or more, more preferably 1100 HV or more, further preferably 1200 HV or more, particularly preferably 1250 HV or more, and most preferably 1300 HV or more.
[0054] On the other hand, the Vickers hardness of the present protective film is, for example, 1800 HV or less, or preferably 1600 HV or less.
[0055] In order to adjust the Vickers hardness to the above range, it is preferable to produce the protective film by the method (present production method) described later.
[0056] The Vickers hardness of the protective film was determined in accordance with JIS Z 2244.
[0057] More specifically, the Vickers hardness of the present protective film is a Vickers hardness (HV 0.005) obtained by using a micro Vickers hardness tester (HM-220, manufactured by Mitutoyo Corporation) with a diamond indenter having an opposing angle of 136° and a load test force of 0.049 N.
[0058] 〈Porosity〉
[0059] Because the present protective film has excellent plasma resistance and appearance, the porosity of the present protective film is less than 0.5% by volume, preferably 0.3% by volume or less, more preferably 0.2% by volume or less, and further preferably 0.1% by volume or less.
[0060] In order to adjust the porosity to the above range, it is preferable to produce the protective film by the method (present production method) described later.
[0061] The porosity of the protective film was determined as follows.
[0062] First, a focused ion beam (FIB) was used to perform tilt processing on the protective film and a portion of the substrate described later in the thickness direction at an angle of 52° from the surface of the protective film toward the substrate to expose the cross section. The exposed cross section was observed using a field emission scanning electron microscope (FE-SEM) at a magnification of 20,000 times, and its cross-sectional image was taken.
[0063] The cross-sectional image is captured at multiple locations. Specifically, for example, when the protective film and the substrate are circular, the image is captured at a total of five points, including one point in the center of the surface of the protective film (or the surface of the substrate) and four points located 10 mm from the periphery, and the size of the cross-sectional image is 6 μm × 5 μm. When the thickness of the protective film is 5 μm or more, the cross-sectional images are captured at multiple shooting locations in a manner that allows the cross section of the entire protective film to be observed in the thickness direction.
[0064] Next, the obtained cross-sectional image was analyzed using image analysis software (ImageJ, manufactured by National Institute of Health) to determine the area of the pore portion in the cross-sectional image. The ratio of the area of the pore portion relative to the area of the entire cross-sectional area of the protective film was calculated and regarded as the porosity of the protective film (unit: volume %). It should be noted that for fine pores (pores with a pore diameter of 20 nm or less) that cannot be detected by image analysis software, their area is regarded as 0.
[0065] <composition>
[0066] The present protective film contains yttrium oxide (Y2O3). The Y2O3 content of the present protective film is preferably 95% by mass or more, more preferably 98% by mass or more, and even more preferably 100% by mass.
[0067] The protective film manufactured by the method described later (the present manufacturing method) is substantially composed of only Y2O3, and the Y2O3 content thereof satisfies the above-mentioned range.
[0068] 〈Orientation degree〉
[0069] When the area of the protective film is increased, from the perspective of suppressing the generation of cracks (including wrinkles, the same applies hereinafter) in the protective film, the orientation degree of the (222) crystal plane of Y2O3 in the protective film (hereinafter also referred to as "orientation degree") is preferably higher.
[0070] Specifically, the degree of orientation is preferably 50% or more, more preferably 65% or more, and even more preferably 80% or more.
[0071] In order to adjust the degree of orientation to the above range, it is preferred to produce the protective film by the method described later (this production method).
[0072] The orientation degree is shown in the XRD pattern of the protective film (refer to Figure 6 ) is the ratio (unit: %) of the peak intensity of the (222) crystal plane when the total peak intensity of each crystal plane of Y2O3 is set to 100.
[0073] The XRD pattern of the protective film was obtained by performing XRD measurement in a microscopic 2D (two-dimensional) mode under the following conditions using an X-ray diffractometer (D8 DISCOVER Plus, manufactured by Bruker Corporation).
[0074] ·X-ray source: CuKα ray (output: 45kV, current: 120mA)
[0075] Scanning range: 2θ=10°~80°
[0076] Step time: 0.2s / step
[0077] Scanning speed: 10° / min
[0078] Step width: 0.02°
[0079] Detector: Multi-mode detector EIGER (2D mode)
[0080] ·Incident side optical system: multi-layer film mirror + Micro Slit+ Collimator
[0081] ·Light receiving side optical system: OPEN
[0082] 〈Crystalline size〉
[0083] As described above, for example, particles (grains) detached from a component exposed to plasma may adhere to a semiconductor substrate and may become foreign matter causing defects in a circuit.
[0084] At this time, the smaller the particle size is, the more the generation of defects can be suppressed.
[0085] Therefore, the crystallite size of the protective film is preferably 40 nm or less, more preferably 30 nm or less, further preferably 20 nm or less, further preferably 15 nm or less, particularly preferably 11 nm or less, more particularly preferably 10 nm or less, very preferably 9 nm or less, and most preferably 8 nm or less.
[0086] On the other hand, the crystallite size of the present protective film is preferably 2 nm or more, more preferably 6 nm or more, and even more preferably 7 nm or more.
[0087] In order to make the crystallite size within the above range, it is preferable to produce the protective film by the method described later (this production method).
[0088] The crystallite size in the protective film was determined using the Scherrer equation based on data of an XRD chart obtained by XRD measurement of the protective film after mirror polishing.
[0089] <thickness>
[0090] The thickness of the protective film is, for example, 0.3 μm or more, preferably 1.0 μm or more, more preferably 1.5 μm or more, further preferably 5 μm or more, particularly preferably 10 μm or more, and most preferably 15 μm or more.
[0091] On the other hand, the thickness of the present protective film is 300 μm or less, preferably 200 μm or less, more preferably 100 μm or less, further preferably 50 μm or less, and particularly preferably 30 μm or less. The thickness of the present protective film may be 10 μm or less.
[0092] The thickness of the protective film is measured as follows.
[0093] The cross section of the protective film was observed using a scanning electron microscope (SEM), the thickness of the protective film was measured at 5 arbitrary points, and the average value of the measured values at the 5 points was regarded as the thickness of the protective film (unit: μm).
[0094] 〈Number of hydrogen atoms〉
[0095] The number of hydrogen atoms in the present protective film is preferably small, so that the present protective film has better plasma resistance.
[0096] The reason is presumably as follows. That is, if the protective film contains more hydrogen, the hydrogen easily reacts with the fluorine contained in the plasma (or the gas used to generate the plasma), and as a result, the protective film is easily damaged. On the other hand, if the protective film contains less hydrogen, the reaction with fluorine is relatively reduced, and the damage to the protective film is suppressed.
[0097] Specifically, the number of hydrogen atoms in the protective film (the number of hydrogen atoms in the film) is preferably 5.0×10 21 Pieces / cm 3 Below, more preferably 4.5×10 21 Pieces / cm 3 Below, more preferably 3.5×10 21 Pieces / cm 3 Below, more preferably 3.0×10 21 Pieces / cm 3 Below, particularly preferably 2.5×10 21 Pieces / cm 3 Below, the most preferred is 2.3×10 21 Pieces / cm 3 the following.
[0098] It should be noted that the hydrogen in the protective film is highly likely to be affected by moisture contained in the base material described later.
[0099] In particular, when the material of the substrate is ceramic, the number of hydrogen atoms in the formed protective film can be reduced by heating the substrate (preheating) before forming the protective film.
[0100] In addition, a method for reducing the number of hydrogen atoms in the protective film will be described below.
[0101] On the other hand, the number of hydrogen atoms in the protective film is preferably 0.1×10 21 Pieces / cm 3 More preferably, 0.5×10 21 Pieces / cm 3 above.
[0102] The number of hydrogen atoms in the protective film was determined by using a secondary ion mass spectrometer (IMS-6f, manufactured by AMETEK) to analyze the primary ion species Cs + , primary acceleration voltage 15.0kV, detection area Calculated at a measurement depth of 500 nm.
[0103] 〈Compression stress〉
[0104] The stress of the protective film (internal stress of the film, residual stress) is not tensile stress, but preferably compressive stress.
[0105] The compressive stress of the present protective film is preferably 100 MPa or more, more preferably 200 MPa or more, and even more preferably 300 MPa or more.
[0106] On the other hand, the compressive stress of the present protective film is preferably 1700 MPa or less, more preferably 1600 MPa or less, and further preferably 1500 MPa or less.
[0107] The compressive stress of the protective film is determined as follows.
[0108] A protective film was formed on a quartz glass substrate, and the surface shape of the formed protective film was measured using a surface shape measuring device (Surfcom NEX241SD2-13, manufactured by Tokyo Seimitsu Co., Ltd.), and the compressive stress (film stress σ) of the protective film was calculated using the Stoney equation (the following equation).
[0109] The Stoney formula is expressed as follows.
[0110] σ=Yd 2 / 6(1-ν)t×8h / c 2 +4h2
[0111] In the above formula, σ: film stress, Y: Young's modulus of the substrate, d: thickness of the substrate, ν: Poisson's ratio of the substrate, t: thickness of the protective film, h: warpage, and c: radius of curvature.
[0112] [part]
[0113] Figure 1 1 is a schematic diagram showing an example of the component 6 .
[0114] The component 6 includes a substrate 5 and an yttrium protective film 4 .
[0115] like Figure 1 As shown, an underlayer (underlayer 1, underlayer 2, and underlayer 3) may be disposed between the substrate 5 and the yttrium protective film 4. However, the number of underlayers is not limited to three.
[0116] The component of the present embodiment (hereinafter also referred to as “the present component”) has the above-mentioned present protective film as the yttrium protective film.
[0117] Since the surface of the present component is covered with the present protective film, the present component has excellent plasma resistance similar to the present protective film.
[0118] Hereinafter, each part included in this component will be described in detail.
[0119] 〈Base Material〉
[0120] The substrate has at least a surface on which the yttrium protective film (or the base layer described below) can be formed. Hereinafter, for convenience, this surface may be referred to as a "film-forming surface".
[0121] Materials
[0122] The material of the base material can be appropriately selected depending on the purpose of the component and the like.
[0123] The substrate is composed of, for example, at least one selected from the group consisting of carbon (C), ceramics, and metals.
[0124] Here, the ceramic is, for example, at least one selected from glass (soda-lime glass, etc.), quartz, aluminum oxide (Al2O3), aluminum nitride (AlN), cordierite, yttrium oxide, silicon carbide (SiC), Si-impregnated silicon carbide, silicon nitride (SiN), sialon and aluminum oxynitride (AlON).
[0125] The Si-impregnated silicon carbide is obtained by heating and melting a Si single substance and impregnating the single substance into silicon carbide (SiC).
[0126] The metal is, for example, at least one selected from aluminum (Al) and an alloy containing aluminum (Al).
[0127] "shape"
[0128] The shape of the substrate is not particularly limited, and examples thereof include a flat plate shape, a ring shape, a dome shape, a concave shape, or a convex shape, and the shape can be appropriately selected depending on the use of the component and the like.
[0129] 《Surface roughness of film-forming surface》
[0130] For reasons described later, the surface roughness of the film-forming surface of the substrate, measured in terms of arithmetic mean roughness Ra, is preferably less than 1.0 μm, more preferably less than 0.6 μm, further preferably less than 0.3 μm, further preferably less than 0.1 μm, particularly preferably less than 0.08 μm, more particularly preferably less than 0.05 μm, very preferably less than 0.01 μm, and most preferably less than 0.005 μm.
[0131] On the other hand, the surface roughness of the film-forming surface of the substrate is preferably 0.01 μm or more, more preferably 0.05 μm or more, and further preferably 0.1 μm or more in terms of arithmetic mean roughness Ra.
[0132] The surface roughness (arithmetic mean roughness Ra) of the film-formed surface was measured in accordance with JIS B0601:2001.
[0133] 《Maximum length of film-forming surface》
[0134] The maximum length of the film-forming surface of the substrate is preferably 30 mm or more, more preferably 100 mm or more, further preferably 200 mm or more, further preferably 300 mm or more, particularly preferably 500 mm or more, very preferably 800 mm or more, and most preferably 1000 mm or more.
[0135] It should be noted that the “maximum length” refers to the maximum length of the film-forming surface, specifically, for example, the diameter of the film-forming surface when viewed from above as a circle, the outer diameter of the film-forming surface when viewed from above as a ring, or the length of the maximum diagonal line of the film-forming surface when viewed from above as a quadrilateral.
[0136] On the other hand, the maximum length of the film-forming surface is, for example, 2000 mm or less, or preferably 1500 mm or less.
[0137] Figure 2 This is a schematic diagram showing a half of the ring-shaped base material 5 cut away.
[0138] for Figure 2 The substrate 5 shown has, for example, an outer diameter D1 of 100 mm, an inner diameter D2 of 90 mm, and a thickness t of 5 mm, and its maximum length is 100 mm.
[0139] Although the substrate 5 has a film-forming surface 7, Figure 2 As shown, the first film forming surface 7 a having a predetermined maximum length (outer diameter D1 ) and the second film forming surface 7 b different from the first film forming surface 7 a may be provided.
[0140] The ratio of the area of the second film-forming surface 7 b to the total area of the film-forming surface 7 is, for example, 60% or less.
[0141] Figure 3 1 is a schematic diagram showing a part of the cross section of another annular base material 5 .
[0142] like Figure 3 As shown, the substrate 5 may have a plurality of second film forming surfaces 7 b.
[0143] Figure 4 1 is a schematic diagram showing a part of the cross section of still another annular base material 5 .
[0144] The angle between the first film forming surface 7a and the second film forming surface 7b is, for example, 20° to 120°. Figure 4 In the illustrated substrate 5 , the angle between the first film-forming surface 7 a and the second film-forming surface 7 b is approximately 30°, and the second film-forming surface 7 b is connected to the first film-forming surface 7 a .
[0145] 〈Basal layer〉
[0146] As described above, one or more underlayers may be disposed between the substrate and the yttrium protective film.
[0147] By forming the base layer, the tensile stress of the yttrium protective film is relaxed and compressive stress is generated, or the adhesion of the yttrium protective film to the substrate is increased.
[0148] The upper limit of the number of base layers is not particularly limited, but is preferably 5 layers or less, more preferably 4 layers or less, further preferably 3 layers or less, particularly preferably 2 layers or less, and most preferably 1 layer.
[0149] The base layer is preferably an amorphous film or a microcrystalline film.
[0150] The base layer preferably contains at least one oxide selected from the group consisting of Al2O3, SiO2, Y2O3, MgO, ZrO2, La2O3, Nd2O3, Yb2O3, Eu2O3 and Gd2O3.
[0151] When two or more underlayers are disposed between the substrate and the yttrium protective film, the oxides of the underlayers are preferably different between adjacent underlayers.
[0152] The so-called case where the oxides of adjacent base layers are different from each other, specifically, for example, the oxide of base layer 1 is "SiO2", the oxide of base layer 2 is "Al2O3+SiO2", and the oxide of base layer 3 is "Al2O3".
[0153] The thickness of each base layer is preferably 0.1 μm or more, more preferably 0.4 μm or more, and further preferably 0.8 μm or more.
[0154] On the other hand, the thickness of the base layer is, for example, 15 μm or less, preferably 10 μm or less, more preferably 7 μm or less, and further preferably 3 μm or less.
[0155] The thickness of the base layer is measured in the same manner as the thickness of the yttrium protective film.
[0156] 〈Use of parts〉
[0157] This member is used as a member such as a top plate inside a semiconductor device manufacturing apparatus (plasma etching apparatus, plasma CVD apparatus, etc.), for example.
[0158] However, the use of this component is not limited to this.
[0159] [Yttrium protective film and method for producing parts]
[0160] Next, a method for manufacturing the yttrium protective film of the present embodiment (hereinafter also referred to as "the present manufacturing method") will be described. The present manufacturing method is also a method for manufacturing the present component described above.
[0161] This production method is a so-called ion-assisted deposition (IAD) method.
[0162] In brief, in a vacuum, while irradiating with ions, an evaporation source (Y2O3) is evaporated and attached to the substrate, thereby forming an yttrium protective film containing Y2O3.
[0163] According to the present manufacturing method, a very dense yttrium protective film can be formed. That is, the obtained yttrium protective film has a small porosity and a small crystallite size.
[0164] However, the thicker the yttrium protective film is, the more likely it is to crack.
[0165] In addition, by increasing the area of the film-forming surface, the area of the yttrium protective film formed on the film-forming surface also increases. In this case, cracks are also likely to occur in the yttrium protective film.
[0166] However, according to the present production method, a dense and hard yttrium protective film can be obtained.
[0167] Furthermore, when the base layer is formed, the tensile stress of the yttrium protective film is relaxed.
[0168] Therefore, the yttrium protective film obtained by the present production method is unlikely to crack even if the thickness or area is increased.
[0169] In addition, the surface roughness (arithmetic mean roughness Ra) of the film-forming surface of the substrate is preferably within the above range. This makes the formed yttrium protective film denser and harder and less likely to crack.
[0170] In addition, when using a method such as a sputtering method, an aerosol deposition (AD) method, and an ion plating (IP) method, many pores tend to remain in the obtained yttrium protective film.
[0171] <Device Configuration>
[0172] based on Figure 5 This production method will be described in more detail.
[0173] Figure 5 This is a schematic diagram showing an apparatus used for producing the yttrium protective film.
[0174] Figure 5 The device shown has a chamber 11. The interior of the chamber 11 can be evacuated by driving a vacuum pump (not shown) to form a vacuum.
[0175] Crucibles 12 and 13 and an ion gun 14 are arranged inside the chamber 11 , and a support 17 is arranged above them.
[0176] The holder 17 is integrated with the support shaft 16, and rotates with the rotation of the support shaft 16. The heater 15 is arranged around the holder 17.
[0177] The substrate 5 is held by the holder 17 in a state where the film-forming surface thereof faces downward. The substrate 5 held by the holder 17 is rotated as the holder 17 rotates while being heated by the heater 15 .
[0178] Furthermore, a quartz crystal film thickness monitor 18 and a quartz crystal film thickness monitor 19 are installed in the chamber 11 .
[0179] 〈Formation of yttrium protective film〉
[0180] right Figure 5 In the device shown, a yttrium protective film ( Figure 5 The situation (not shown in the figure) is explained below.
[0181] First, one or both of the crucible 12 and the crucible 13 are filled with the evaporation source Y 2 O 3 .
[0182] After the substrate 5 is held on the holder 17 , the interior of the chamber 11 is evacuated to form a vacuum.
[0183] Next, the holder 17 is rotated while the heater 15 is driven. Thus, the substrate 5 is rotated while being heated.
[0184] In this state, ion-assisted vapor deposition is performed to form a film on the substrate 5 .
[0185] That is, while ion gun 14 irradiates ions (ion beam), evaporation source Y 2 O 3 filled in one or both of crucible 12 and crucible 13 is evaporated.
[0186] The ions irradiated by the ion gun 14 are preferably ions of at least one element selected from the group consisting of oxygen, argon, neon, krypton, and xenon.
[0187] The evaporation source is melted and evaporated by irradiation with an electron beam (not shown).
[0188] As a result, the evaporated evaporation source adheres to (the film formation surface of) the substrate 5, and an yttrium protective film is formed.
[0189] 《Pressure in the chamber》
[0190] The film formation is performed in a vacuum. Specifically, the pressure inside the chamber 11 is preferably 6×10 -2 Pa or less, more preferably 5×10 -2 Pa or less, more preferably 3×10 -2 Below Pa.
[0191] On the other hand, the pressure inside the chamber 11 is preferably greater than 1×10 -6 Pa, preferably 1×10 -5 Pa or more, more preferably 1×10 -4 Pa or above.
[0192] Temperature of the substrate
[0193] During film formation, the temperature of the substrate 5 heated by the heater 15 is preferably 200° C. or higher, more preferably 250° C. or higher.
[0194] On the other hand, the temperature is preferably 400°C or lower, more preferably 350°C or lower.
[0195] Film forming speed
[0196] The speed (film formation speed) at which the evaporation sources of the crucibles 12 and 13 evaporate to form a film is monitored in advance using the crystal film thickness monitor 18 and the crystal film thickness monitor 19 , respectively.
[0197] The film formation rate is adjusted by controlling the conditions of the electron beam irradiated to the evaporation source and the conditions of the ion beam of the ion gun 14 (current value, current density, etc.).
[0198] In forming the yttrium protective film, the film formation rate (unit: nm / min) of each evaporation source is adjusted to a desired value.
[0199] The film formation rate of the evaporation source Y2O3 is preferably 1 nm / min or more, more preferably 1.5 nm / min or more, and further preferably 2 nm / min or more.
[0200] The film formation rate of the evaporation source Y2O3 is preferably 20 nm / min or less, more preferably 15 nm / min or less, and further preferably 10 nm / min or less.
[0201] 《Conditions of ion irradiation》
[0202] The distance between the ion gun 14 and the substrate 5 is preferably 700 mm or more, more preferably 900 mm or more. On the other hand, the distance is preferably 1500 mm or less, more preferably 1300 mm or less.
[0203] The current value of the ion beam is preferably 1000 mA or more, and more preferably 1500 mA or more. On the other hand, the current value of the ion beam is preferably 3000 mA or less, and more preferably 2500 mA or less.
[0204] The ion beam current density is preferably 40 μA / cm2 because the obtained yttrium protective film becomes harder. 2 More preferably, 65 μA / cm 2 More preferably, 75 μA / cm 2 Above, particularly preferably 77 μA / cm 2 above.
[0205] On the other hand, the ion beam current density is preferably 140 μA / cm 2 Below, more preferably 120μA / cm 2 Below, more preferably 100 μA / cm 2 the following.
[0206] 〈Formation of the basal layer〉
[0207] It is preferable to form the above-mentioned base layers (for example, base layer 1 , base layer 2 , and base layer 3 ) on the film formation surface of the substrate 5 before forming the yttrium protective film.
[0208] The base layer is formed by ion-assisted vapor deposition in the same manner as the yttrium protective film.
[0209] For example, when forming a base layer composed of Al2O3, Al2O3 is filled into one or both of the crucibles 12 and 13 as an evaporation source, and while irradiating ions (ion beam) with the ion gun 14, the evaporation source is evaporated and attached to the film forming surface of the substrate 5.
[0210] The conditions for forming the base layer are based on the conditions for forming the yttrium protective film.
[0211] However, the base material sometimes contains crystal water.
[0212] For example, when an alumina (Al 2 O 3 ) substrate is heated from room temperature, generation of crystal water from a hydrate of a low temperature stable phase of alumina (eg, boehmite γ-alumina) is observed at around 520°C.
[0213] If the formed yttrium protective film contains water generated from the crystal water of the substrate, the number of hydrogen atoms in the yttrium protective film tends to increase.
[0214] Therefore, before the evaporation source Y2O3 is attached to the film-forming surface of the substrate (that is, before the yttrium protective film is formed), a base layer is formed on the film-forming surface of the substrate.
[0215] This is preferred because at least the film-forming surface of the substrate is covered, and thus the crystal water of the substrate is less likely to be included in the formed yttrium protective film, and the number of hydrogen atoms in the yttrium protective film is reduced.
[0216] 〈Preheating of substrate〉
[0217] Similar to the formation of the base layer, because it is not easy to include the crystal water of the substrate in the yttrium protective film, it is preferred to heat the substrate at a high temperature (preheating) before allowing the evaporation source Y2O3 to adhere to the film-forming surface of the substrate (i.e., forming the yttrium protective film).
[0218] The preheating temperature is preferably 300° C. or higher, more preferably 400° C. or higher, further preferably 450° C. or higher, particularly preferably 500° C. or higher.
[0219] On the other hand, the preheating temperature is, for example, 800° C. or lower, preferably 750° C. or lower, and more preferably 700° C. or lower.
[0220] The preheating time is preferably 60 minutes or longer, more preferably 120 minutes or longer, further preferably 240 minutes or longer, particularly preferably 480 minutes or longer.
[0221] On the other hand, the preheating time is preferably 1200 minutes or less, more preferably 1000 minutes or less, further preferably 800 minutes or less, and particularly preferably 600° C. or less.
[0222] The preheated atmosphere is, for example, an air atmosphere.
[0223] Example
[0224] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited to the Examples described below.
[0225] Hereinafter, Examples 1 to 27, Examples 30 to 31, and Examples 39 to 42 are embodiments, Examples 28 to 29, Examples 32 to 33, and Examples 37 to 38 are comparative examples, and Examples 34 to 36 are reference examples.
[0226] 〈Example 1〉
[0227] Use based Figure 5 The described apparatus was used to produce a yttrium protective film (protective film) under the conditions shown in Table 1 below.
[0228] As the substrate, a circular substrate (thickness: 10 mm) made of aluminum oxide (Al 2 O 3 ) and having a film-forming surface having a diameter (maximum length) of the value shown in Table 1 below was used.
[0229] The substrate was preheated in the air atmosphere while being held on a holder in the chamber. The preheating temperature was the temperature shown in Table 1 below (unit: °C), and the preheating time was 600 minutes. When the substrate was not preheated, "-" was recorded in the column of the preheating temperature.
[0230] Next, the base layer and the yttrium protective film (protective film) shown in Table 1 below were formed on the film formation surface of the substrate under the production conditions shown in Table 1 below.
[0231] As manufacturing conditions not shown in Table 1 below, oxygen (O) ions were irradiated from an ion gun, the distance between the ion gun and the substrate was 1100 mm, and the current value of the ion beam was 2000 mA.
[0232] Figure 6 This is the XRD pattern of the yttrium protective film of Example 1.
[0233] like Figure 6 As shown, it can be seen that in the yttrium protective film of Example 1, the most closely packed crystal plane of the cubic crystal structure, namely the (222) crystal plane, is preferentially oriented.
[0234] The yttrium protective film of Example 1 was observed using a SEM at a magnification of 50,000 times.
[0235] Figure 7 This is a surface SEM photograph of the yttrium protective film of Example 1. Figure 8 This is a cross-sectional SEM photograph of the yttrium protective film of Example 1.
[0236] like Figure 7 and Figure 8 As shown, it can be seen that the yttrium protective film of Example 1 is very dense and excellent in smoothness. In addition, it can be seen that the particle size is uniform.
[0237] 〈Example 2~Example 33〉
[0238] In Examples 2 to 33, one or two or more conditions were changed from those in Example 1. A yttrium protective film (protective film) was produced in the same manner as in Example 1 except for the above.
[0239] In summary, for example, it is as follows. It should be noted that in each example, in addition to the following description, there may be a case where the example 1 is changed.
[0240] In Example 2, the ion beam current density was changed from that in Example 1.
[0241] In Examples 3 to 6, the number of layers and / or the composition of the base layer were changed from that in Example 1.
[0242] In Examples 7 to 10, no base layer was formed.
[0243] In Examples 11 to 20, the substrate and / or base layer were changed from that in Example 1.
[0244] In addition, in Example 13, commercially available soda-lime glass was used as the substrate (glass).
[0245] In Example 15, one side of a substrate composed of an aluminum single crystal was subjected to an alumite treatment and then polished to produce an underlayer composed of Al2O3. This underlayer is described as "anlumite layer" in Table 1 below.
[0246] In Example 16, one side of an aluminum substrate was anodized using oxalic acid to prepare an underlayer composed of Al2O3. This underlayer is described as "anodized layer" in Table 1 below.
[0247] In Examples 21 and 22, the thickness of the protective film was changed from that in Example 1.
[0248] In Examples 23 and 24, the area of the film-forming surface was changed from that in Example 1.
[0249] In Examples 25 to 29, the pressure in the chamber was changed from that in Example 1. It should be noted that the protective film in Example 28 was amorphous (therefore, "-" was written in the column of "degree of orientation").
[0250] In Examples 30 and 31, the film forming speed was changed from that in Example 1.
[0251] In Examples 32 and 33, the surface roughness (Ra) of the film-forming surface was changed from that in Example 1.
[0252] 〈Example 34~Example 36〉
[0253] In Example 34, sapphire is made into a protective film.
[0254] In Example 35, metallic aluminum is made into a protective film.
[0255] In Example 36, quartz is made into a protective film.
[0256] 〈Example 37~Example 38〉
[0257] In Example 37, the IP method was used instead of the IAD method to form a protective film of Y2O3.
[0258] In Example 38, the IAD method is not used, but the CVD method is used to form the Y2O3 protective film.
[0259] 〈Example 39~Example 42〉
[0260] In Examples 39 to 42, protective films were formed in the same manner as in Examples 7, 1, 3, and 26, respectively, except that the substrate was not preheated.
[0261] 〈Properties of protective film〉
[0262] The number of hydrogen atoms, Vickers hardness, porosity, crystallite size, orientation degree, thickness, and compressive stress of the protective film of each example were determined based on the above-mentioned method. The results are shown in Table 1 below.
[0263] In addition, the compressive stress is described as a negative number.
[0264] 〈Etching amount〉
[0265] The protective film of each example was subjected to ion etching and / or radical etching to evaluate plasma resistance.
[0266] Specifically, first, a surface of 10 mm×5 mm in the protective film was mirror-finished, and a Kapton tape was attached to a portion of the mirror-finished surface (referred to as a “test surface”) for masking.
[0267] Next, a test (exposure test) was performed by discharging in a gas described later under the conditions of a pressure of 10 Pa and an RF power of 600 W using a CCP type plasma etching apparatus to generate plasma, and exposing the test surface to the generated plasma.
[0268] In the ion etching, discharge (generation of plasma) is performed using CF 4 gas (flow rate: 100 sccm) and O 2 gas (flow rate: 100 sccm), and CF 4 ions are generated in the plasma.
[0269] In the radical etching, discharge (plasma generation) is performed using CF 4 gas (flow rate: 100 sccm), Ar gas (flow rate: 50 sccm) and O 2 gas (flow rate: 100 sccm), and F radicals are generated in the plasma.
[0270] The discharge (generation of plasma) for 15 minutes was repeated five times, and the exposure test was performed for a total of 150 minutes. Thus, the non-shielded portion of the test surface was etched.
[0271] Then, the etching amount was determined by measuring the difference in level between the shielded portion and the non-shielded portion of the test surface using a stylus-type surface profile measuring machine (manufactured by ULVAC, Dectak 150).
[0272] In addition, when ion etching or radical etching was not performed, "-" was recorded in the following Table 1.
[0273] The smaller the etching amount (unit: nm), the better the plasma resistance can be evaluated.
[0274] Specifically, when the etching amount (ion etching amount, radical etching amount) is 200 nm or less, it can be evaluated that the plasma resistance is excellent.
[0275] 〈Appearance〉
[0276] The appearance of the formed protective film was visually observed to confirm whether cracks (including wrinkles; the same applies hereinafter) were generated.
[0277] In Table 1 below, cracks of 1.0 mm or more are recorded as "present", cracks of less than 1.0 mm are recorded as "slight", and no cracks are recorded as "absent". If "slight" or "absent", the appearance can be evaluated as excellent.
[0278] In the case of "slight", although fine cracks were generated on the edge surfaces of the protective film, no cracks were generated in the center portion of the protective film.
[0279] [Table 1]
[0280]
[0281]
[0282]
[0283] 〈Summary of evaluation results〉
[0284] As shown in Table 1, the yttrium protective films of Examples 1 to 27 and Examples 30 to 31 are excellent in plasma resistance and appearance. In contrast, the yttrium protective films of Examples 28 to 29, Examples 32 to 33, and Examples 37 to 38 are insufficient in at least one of plasma resistance and appearance.
[0285] Several examples are explained below.
[0286] Example 2: By reducing the ion beam current density, the compressive stress of the protective film is reduced.
[0287] Examples 8 to 10: As the surface roughness of the film-forming surface increases, the compressive stress of the protective film decreases.
[0288] Example 12: Since the film formation speed is increased, the effect of ion irradiation becomes smaller and the compressive stress of the protective film is reduced.
[0289] Example 13: In an example using soda-lime glass as a substrate, the compressive stress of the protective film is reduced by lowering the temperature of the substrate.
[0290] Examples 26 and 27: Since the pressure in the chamber during film formation was reduced, the mean free path became longer, and the kinetic energy generated by the collision between the irradiated ions and the particles (evaporation source) became larger, thereby increasing the compressive stress of the protective film.
[0291] Example 28: Since the film formation speed is increased, the effect of ion irradiation becomes smaller and the compressive stress of the protective film is reduced.
[0292] Example 29: By reducing the ion beam current density, the compressive stress of the protective film is reduced.
[0293] Example 30: Since the temperature of the evaporation source is lowered, the crystal growth slows down and the compressive stress of the protective film is reduced.
[0294] Example 31: Since the pressure in the chamber during film formation is reduced, and thus the film formation speed is reduced, the effect of ion irradiation becomes greater and the compressive stress of the protective film increases.
[0295] Examples 32 to 33: Since the pressure in the chamber during film formation was reduced, the mean free path became longer, and the kinetic energy generated by the collision between the irradiated ions and the particles (evaporation source) became larger, thereby increasing the compressive stress of the protective film.
[0296] Examples 39 to 42: Since the substrate was not preheated, the number of hydrogen atoms in the protective film increased compared to Examples 7, 1, 3, and 26 in which the substrate was preheated.
[0297] It should be noted that the entire contents of the specifications, claims, drawings, and abstracts of Japanese Patent Application No. 2022-131021 filed on August 19, 2022 and Japanese Patent Application No. 2022-175428 filed on November 1, 2022 are incorporated herein by reference and incorporated as a disclosure of the present invention.
[0298] Explanation of symbols
[0299] 1, 2, 3: Basal layer
[0300] 4: Yttrium protective film
[0301] 5: Base material
[0302] 6: Parts
[0303] 7: Film-forming surface
[0304] 7a: First film-forming surface
[0305] 7b: Second film-forming surface
[0306] 11: Chamber
[0307] 12, 13: Crucible
[0308] 14: Ion Gun
[0309] 15: Heater
[0310] 16: Support shaft
[0311] 17: Bracket
[0312] 18, 19: Crystal film thickness monitor
Claims
1. A yttrium protective film containing yttrium oxide, having a porosity of less than 0.5% by volume and a Vickers hardness of 800 HV or more.
2. The yttrium protective film according to claim 1, wherein: The thickness is 0.3 μm or more.
3. The yttrium protective film according to claim 1, wherein: The thickness is 15 μm or less.
4. The yttrium protective film according to claim 1, wherein: The crystallite size is less than 40 nm.
5. The yttrium protective film according to claim 1, wherein: The crystallite size is 6 nm or more.
6. The yttrium protective film according to claim 1, wherein: The orientation degree of the (222) crystal plane of Y2O3 is greater than 50%.
7. The yttrium protective film according to claim 1, wherein: The number of hydrogen atoms is 5.0×10 21 Pieces / cm 3 the following.
8. The yttrium protective film according to claim 1, wherein: The compressive stress is 100~1700MPa. 9 . A component comprising: a substrate; and the yttrium protective film according to claim 1 , which is disposed on a surface of the substrate, namely, a film-forming surface.
10. The component according to claim 9, wherein The substrate is composed of at least one selected from carbon, ceramics and metals, The ceramic is at least one selected from glass, quartz, alumina, aluminum nitride, cordierite, yttrium oxide, silicon carbide, Si-impregnated silicon carbide, silicon nitride, sialon and aluminum oxynitride, The metal is at least one selected from the group consisting of aluminum and an alloy containing aluminum.
11. The component according to claim 9, wherein The substrate is composed of aluminum oxide.
12. The component according to claim 9, wherein The substrate is composed of quartz.
13. The component according to claim 9, wherein The surface roughness of the film-forming surface is less than 1.0 μm in terms of arithmetic mean roughness Ra.
14. The component according to claim 9, wherein The surface roughness of the film-forming surface is 0.01 μm or more in terms of arithmetic mean roughness Ra.
15. The component according to claim 9, wherein The maximum length of the film-forming surface is greater than 30 mm.
16. The component according to claim 9, wherein There is one or more base layers between the substrate and the yttrium protective film, The base layer contains at least one oxide selected from Al2O3, SiO2, Y2O3, MgO, ZrO2, La2O3, Nd2O3, Yb2O3, Eu2O3 and Gd2O3.
17. The component according to claim 16, wherein There are two or more base layers between the substrate and the yttrium protective film, The oxides are different from each other in adjacent base layers.
18. The component according to claim 9, wherein The substrate has a first film-forming surface with a predetermined maximum length and a second film-forming surface different from the first film-forming surface as the film-forming surface, The angle between the first film forming surface and the second film forming surface is 20° to 120°, A ratio of the area of the second film-forming surface to the total area of the film-forming surface is 60% or less.
19. The component according to claim 9, which is used inside a plasma etching device or a plasma CVD device.
20. A method for producing a yttrium protective film, the method comprising: irradiating ions of at least one element selected from oxygen, argon, neon, krypton and xenon in a vacuum while evaporating an evaporation source to attach the ions to a substrate; As the evaporation source, Y2O3 was used.
21. The method for producing a yttrium protective film according to claim 20, wherein: Before attaching the evaporation source to the substrate, the substrate is heated at 300° C. or higher.
22. The method for manufacturing a yttrium protective film according to claim 20, wherein: Before attaching the evaporation source to the substrate, forming one or more base layers on the surface of the substrate, The base layer contains at least one oxide selected from Al2O3, SiO2, Y2O3, MgO, ZrO2, La2O3, Nd2O3, Yb2O3, Eu2O3 and Gd2O3.
Citation Information
Patent Citations
Material for spray coating, sprayed coating, and member with sprayed coating
JP2018076546A
Watch
JP2022131021A
Umbrella and manufacturing method of the same
JP2022175428A